HUBUNGAN TINGKAT PENGETAHUAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DENGAN PERILAKU SADARI PADA MAHASISWI NON KESEHATAN DI UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Baswedan, Rizki Hafidzah; Listiowati, Ekorini (Biomedika, 2014)
Breast cancer is a type of malignant tumor that most commonly affects women around the world, both in the developed and developing countries, as evidenced by the discovery of 1:38 million new cases and 458 400 deaths from breast cancer in 2008. In Indonesia, breast cancer is now the number one killer and every year there are an estimated 100 new cases per 100,000 population in Indonesia. This can be prevented by spreading knowledge about cancer and early detection by performing routine breast self-examination. The American Cancer Society recommends breast self-examination performed on women aged 20 years. Students of non-health is one component of society that have a high level of knowledge, but less exposure to health problems.This study uses observational analytic with cross sectional approach. The subjects of this study were non-health students from Islamic faculty, agriculture faculty, and engineering faculty. The number of samples in this study was 209 respondents. The level of knowledge about breast tumor, BSE, and BSE behavior was assessed using a questionnaire followed by interview. The results obtained were processed using a computerized system with the Spearman correlation test.The results showed that there is a relationship between the level of knowledge about BSE and BSE behavior in non-health student although statistical tests showed no signifi cant correlation p 0.680 (p> 0.05). The relationship between the level of knowledge about BSE and BSE behavior on non-health student infl uenced by various factors including experience, education, resources, and bridged by a positive attitude.Keywords: Knowledge Level, Behaviour, Breast Self-Examination (BSE), Non-health Students